2022
DOI: 10.21037/apm-21-740
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic thigh abscess caused by Streptococcus constellatus subsp. constellatus in a patient with exacerbation of bronchiectasis: a case report

Abstract: Streptococcus constellatus (S. constellatus) is a Gram-positive commensal bacterium that is commonly found in the oral, nasal, pharyngeal, gastrointestinal, and urogenital tracts. It can be further consisted by three subspecies: subsp, constellatus, subsp. pharynges, and subsp. viborgensis. As an opportunistic pathogen, S. constellatus can cause abscesses and bacteremia, so infection requires timely and accurate identification in clinical practice. There are a few case reports describing the range of infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…First, NGS is not absolute in detecting pathogenic bacteria and there is also a possibility of missing detection. [ 6 ] Second, if a positive result is found, a drug sensitivity test cannot be performed to clarify the drug susceptibility of the organism compared to traditional pathogenic tests such as blood and sputum cultures. Third, the NGS is relatively expensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, NGS is not absolute in detecting pathogenic bacteria and there is also a possibility of missing detection. [ 6 ] Second, if a positive result is found, a drug sensitivity test cannot be performed to clarify the drug susceptibility of the organism compared to traditional pathogenic tests such as blood and sputum cultures. Third, the NGS is relatively expensive.…”
Section: Discussionmentioning
confidence: 99%
“…We searched PubMed database for cases of S constellatus over the last decade and found that almost cases reported abscess formation ranging from the brain, orbit, lung, and mediastinum to the heart, ovaries, kidney, liver, spine, and thighs. [6][7][8][9][10][11] We complied 6 cases of DNM caused by S constellatus, and this was the second case of such severe, rapidly progressing septic shock (Table 1). [11][12][13][14][15][16] In another case, which was also very aggressive, a patient developed necrotizing fasciitis in the maxillofacial region, neck, and upper mediastinum after experiencing cold and fatigue, followed by rapid decompensation with resulting septic shock caused by S constellatus and Klebsiella oxytoca.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic infections of Streptococcus constellatus originating from a source in the head and neck are not uncommon [5]. This group of bacteria can cause a wide variety of infections; the most severe being bacteremia and distant focal infections or abscesses involving the central nervous, pulmonary and hepatic systems as well as soft tissues [4,[7][8][9]. Our patient had multiple liver abscesses and although these are traditionally associated with Escherichia coli and Klebsiella pneumoniae, one case series in the USA found Streptococci to be the most common pathogen [10].…”
Section: ' Discussionmentioning
confidence: 99%